An Overview on Microemulsion as a Topical Drug Delivry System - Nishigandha, Naikawadi; Prakash, Jadhav; Avinash, Bhagwat; Atish, Velhal; Vivek Kumar, Redasani; Mayuri, More (Asian Journal of Pharmaceutical Research and Development, 2023)
Due to their extended shelf life, enhanced drug solubilization, and simplicity in preparation and administration, microemulsions are among the greatest possibilities for new drug delivery systems. Microemulsions are liquid mixtures of amphiphile, water, and oil that are thermodynamically stable and optically isotropic. They have become cutting-edge drug delivery systems that enable controlled or sustained release for parenteral, ophthalmic, percutaneous, topical, and transdermal medication administration.Because of their low viscosity, transparency, and, more precisely, their thermodynamic stability, microemulsions may be easily distinguished from regular emulsions. Microemulsions have a wide range of uses and applications, including in the pharmaceutical, agrochemical, cutting oil, biotechnology, food, and cosmetic industries as well as in analytical applications and environmental detoxification. This review paper's main goal is to talk about using microemulsions as a medicine delivery mechanism with other potential uses.